1995
DOI: 10.1002/1097-0142(19950815)76:4<669::aid-cncr2820760420>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Papillary renal tumors. Morphologic, cytochemical, and genotypic features

Abstract: Background. Papillary renal tumors lack alterations of chromosome 3 and show trisomy of chromosomes 7 and 17, genotypic features distinct from nonpapillary carcinomas. Methods. The authors examined 39 papillary renal neoplasms to identify morphologic features allowing distinction of high grade from low grade tumors. Twenty‐nine papillary tumors and 13 nonpapillary tumors were examined for the presence of trisomy of chromosome 7 using fluorescence in situ hybridization. Data recorded included tumor size, stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 15 publications
2
28
0
1
Order By: Relevance
“…17,[23][24][25][26][27][28][34][35][36] The typical gains of chromosome 7 and 17 and loss of Y in papillary renal cell carcinomas have been observed in several FISH-based studies, and FISH analyses with centromeric probes for chromosomes 7, 17 and Y have been previously proposed to have a potential role in the differential diagnosis of papillary renal cell tumors with metanephric adenomas. 25,27,32,35,37 Furthermore, recent studies performed with multicolor FISH confirmed the typical chromosomal abnormalities described in papillary renal cell carcinomas and interphase FISH may be considered as a sensitive and specific technique for a rapid and accurate identification of distinctive genetic abnormalities, that are potentially useful in the distinction of the different histotypes of renal cell carcinomas. 38,39 In conclusion, analysis of chromosomes 7, 17 and Y by FISH with centromeric probes showed that mucinous tubular and spindle cell carcinomas lack the gains of chromosomes 7 and 17 and losses of chromosome Y, that are prevalent in papillary renal cell carcinomas, and may be helpful in the differential diagnosis with classic and sarcomatoid papillary renal cell carcinomas.…”
Section: Discussionmentioning
confidence: 78%
“…17,[23][24][25][26][27][28][34][35][36] The typical gains of chromosome 7 and 17 and loss of Y in papillary renal cell carcinomas have been observed in several FISH-based studies, and FISH analyses with centromeric probes for chromosomes 7, 17 and Y have been previously proposed to have a potential role in the differential diagnosis of papillary renal cell tumors with metanephric adenomas. 25,27,32,35,37 Furthermore, recent studies performed with multicolor FISH confirmed the typical chromosomal abnormalities described in papillary renal cell carcinomas and interphase FISH may be considered as a sensitive and specific technique for a rapid and accurate identification of distinctive genetic abnormalities, that are potentially useful in the distinction of the different histotypes of renal cell carcinomas. 38,39 In conclusion, analysis of chromosomes 7, 17 and Y by FISH with centromeric probes showed that mucinous tubular and spindle cell carcinomas lack the gains of chromosomes 7 and 17 and losses of chromosome Y, that are prevalent in papillary renal cell carcinomas, and may be helpful in the differential diagnosis with classic and sarcomatoid papillary renal cell carcinomas.…”
Section: Discussionmentioning
confidence: 78%
“…Metanephric adenoma, an uncommon benign tumor, can show morphological similarities to some papillary renal cell carcinomas and epithelial-predominant however, compression of the papillary structures can result in more solid architectural patterns. 19 It is in these instances that the differential diagnosis includes metanephric adenoma. Microscopically, most nephroblastomas are triphasic, containing blastemal cells and epithelial and stromal elements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the hypovascular papillary renal carcinomas have different biological characteristics compared to hypervascular conventional (clear cell) renal carcinomas. [25][26][27] These results suggest that AM and VEGF may be in concert with the forming histopathologic character and AM may play a role in tumor growth in conjunction with VEGF, which induces tumor angiogenesis in RCC. Zhao et al reported that AM strongly stimulated endothelial cell growth and acted as an angiogenic factor.…”
Section: Discussionmentioning
confidence: 99%